On the issue of reasons for instituting criminal proceedings (The aspects of the new Criminal Procedure Code edition) - I. V. Makeeva (Путеводитель предпринимателя)
The article’s issue is analyzes of reasons for instituting of criminal proceedings in the sphere of the latest Criminal Procedure Code edition. The interrelation of definitions «the applicant’s safety» and «the applicant’s anonymity» in the article is described. The author gives the legal assessment of investigators’ action while checking case papers derived from a prosecutor.